2022
DOI: 10.1016/j.smhs.2022.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of two COVID-19 lockdowns on physical activity of school-age children

Abstract: The introduction of strict quarantine restrictions in many countries initiated a direction in science to study the behavioral characteristics of children and adolescents during the social isolation at the population level. We present our observations during the two lockdowns in Ukraine. The objective of this study was to determine: a) the level of light (LPA) and moderate-to-vigorous (MVPA) physical activity among school-age children, and b) the impact of the external and internal factors on their physical act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Also, this reduction of PA related to changes in body weight, eating and health habits, in adolescents. Moreover, the results of the present study are in line with studies which used parents' reports about their children's PA level, showing a decreased in PA level and an increase in sedentary behavior (Yelizarova et al, 2022;Alghadir et al, 2021;Chambonniere et al 2021;Kovacs et al, 2021;Stverakova et al, 2021;Wunsch et al, 2021;Dunton et al, 2020;Moore et al, 2020;Schmidt et al, 2020;Seculic et al, 2020). Two Greek research studies have found similar results with the present study, showing insufficient levels of PA only during the first lockdown, in adolescents (Androutsos et al 2021;Morres et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Also, this reduction of PA related to changes in body weight, eating and health habits, in adolescents. Moreover, the results of the present study are in line with studies which used parents' reports about their children's PA level, showing a decreased in PA level and an increase in sedentary behavior (Yelizarova et al, 2022;Alghadir et al, 2021;Chambonniere et al 2021;Kovacs et al, 2021;Stverakova et al, 2021;Wunsch et al, 2021;Dunton et al, 2020;Moore et al, 2020;Schmidt et al, 2020;Seculic et al, 2020). Two Greek research studies have found similar results with the present study, showing insufficient levels of PA only during the first lockdown, in adolescents (Androutsos et al 2021;Morres et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, significant decreases in PA reported among boys, in a study in Croatia (Sekulic et al, 2020). On the contrary, two studies found that PA and perceived MVPA to be higher in adolescent boys, compared to girls both strict lockdowns (Yelizarova et al, 2022;Ng et al, 2021).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Compared to the absence of lockdown, the pandemic reduced by up to 61% the levels of physical activity in people with ID [ 14 ]. In this sense, de-schooling due to the COVID-19 pandemic decreased the possibilities of socialization through group activities and interactions among schoolchildren, heightening non-compliance with the recommendations of physical activity for this population, which suggest an average of 60 min/day of physical activity at moderate and vigorous intensity in children under 18 years of age [ 15 ]. In addition, a decrease in explosive muscle actions related to strength and power were observed [ 16 ], together with muscle disuse due to a lack of motor stimuli [ 17 ] and exercise deficit disorder, accompanied by problems such as pediatric dynapenia and physical illiteracy [ 18 ].…”
Section: Introductionmentioning
confidence: 99%